Bilateral Acute Angle-Closure Glaucoma Induced By Escitalopram - Dilbade Yıldız Ekinci; Zafer Cebeci; Şerife Bayraktar; Belgin İzgi (Türk Oftalmoloji Dergisi)
Escitalopram is an antidepressant of the selective serotonin reuptake inhibitor(SSRI) class. In this manuscript, we report the case of a female patient who developed bilateral acute angle-closure glaucoma induced by escitalopram. A 46-year-old female patient was admitted to our ophthalmology clinic with complaints of severe pain around the both eyes, headache, nausea, and vomiting for two days. In her past medical history, she was using escitalopram for depression for two years. Visual acuity was at hand movement level in both eyes. Anterior segment examination showed bilateral diffuse conjunctival hyperemia, corneal edema, shallow anterior chamber, and fixed dilated pupils. Intraocular pressure was 47 mmHg in the right and 68 mmHg in the left eye. The diagnosis was acute angle-closure glaucoma, and the escitalopram medication was discontinued. She was treated with topical and systemic antiglaucomatous medication. After the cornea become clear, bilateral peripheral laser iridotomy was done. In the following year, she did not begin escitalopram medication again and no other acute angle-closure attack was seen. (Turk J Ophthalmol 2014; 44:396-9)